PERLINDUNGAN HUKUM ATAS HAK PASIEN DARI PENYELESAIAN SENGKETA MEDIK ANTARA PASIEN DENGAN DOKTER DAN/ATAU TENAGA MEDIS SERTA RUMAH SAKIT - Istiana Heriani (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2019)
This study aims to answer the problems in medical disputes why patients often experience difficulties in realizing their rights. The second problem in this research is to answer which forms and dispute resolution systems that provide legal protection to patients in resolving medical disputes between patients and doctors and / or medical personnel and hospitals to realize patient rights. These problems are examined and examined by normative legal research methods and using secondary data consisting of primary legal material and secondary legal material. The results of this study harmonize the laws and regulations with the real situation in the community. Psychological factors, educational and economic factors of patients cause patients to have difficulty in fighting for their rights in medical disputes. Medical dispute resolution that is pursued through litigation and nonlitigation channels are still found weaknesses that have not been in favor of patients. Thus an idea is found through discussion and research conducted previously, that it is necessary to establish a special forum for medical dispute resolution that is in favor of patients as consumers of health services.